A Comparison of Residence Hall Experience for Students of Different Backgrounds. Issue 3 (27th May 2019) - Chu, Sam; Chau, Albert; Chung, Robert; Chong, Eric; Ong, Elsie; Tam, Angie
Abstract : The current study explored the impact of students' residence hall experience in terms of academic, social and personal development and students' motivation to join residence hall activities at a Hong Kong university. The results revealed significant differences, with females, local and non-first-year student groups reporting more gains from their residential hall experience relative to male, non-local and first-year students. Findings are useful in the refinement of the residence hall system to cater for students of diverse backgrounds.